Towards a Framework for Managing Junior Faculty Mentoring in Higher Education: Lessons from Vietnam - Thuy, Le Thi Bich (International Journal of Research in Vocational Studies (IJRVOCAS), 2025)
This conceptual paper proposes a structured framework for managing junior faculty mentoring in higher education institutions (HEIs), with a focus on the Vietnamese context. While mentoring is globally recognized as a core faculty development strategy, its implementation in systems such as Vietnam remains largely informal, fragmented, and weakly integrated into institutional management structures. To address this gap, the study draws on Human Resource Development (HRD), Organizational Learning (OL) theory, and Social Exchange Theory (SET), combined with a review of international mentoring models and the specific characteristics of Vietnam’s higher education environment. The proposed framework comprises six interrelated components: Inputs, Core Processes, Management Layer, Outputs, Evaluation and Feedback, and Contextual Factors. These components are designed to align mentoring activities with institutional development priorities while reflecting cultural and governance realities. The framework emphasizes centralized coordination alongside departmental flexibility, formal mentor and mentee relationships supported by institutional incentives, and continuous evaluation mechanisms adapted to Vietnam’s regulatory context. Although conceptual in scope, the framework offers a theoretically grounded and practice-oriented basis for managing mentoring in Vietnamese HEIs. It provides actionable insights for institutional leaders, policy-makers, and faculty members, while contributing to mentoring literature through its focus on management-oriented approaches in non-Western higher education systems.